Formation of De Geer Moraines Deposited Subglacially, Central Québec - Beaudry, Luc; Prichonnet, Gilbert (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1995)
ABSTRACTThis paper presents a model for the genesis of De Geer moraines in the Chapais and Radisson areas, Québec. The model is mainly based on faciès and deformation structure analysis. Three facies associations have been identified: (1) sorted sediments that form foreset laminations dipping downglacier. Till lenses or glacial diamictons are found within the sorted sediments or form a surficial layer on the proximal side of the sections; (2) a non-fissile and poorly compacted till overlies and deforms sorted sediments. Laminae of finely sorted sediments may be incorporated in the till; (3) a fissile and compact till commonly lies on the basal till sheet. All three facies associations feature deformation structures (faults, folds, load and drag structures) which indicate an upglacier origin. The model proposed is an emplacement of De Geer moraines in bottom crevasses by an active glacier. In areas where meltwaters were channelized, sediments accumulated in the crevasses as foreset laminations. Till filled the crevasses in areas remote from meltwater flow. Glacial activity remobilized the basal till locally and pushed it toward bottom crevasses located downglacier, or overturned large layers of till. Finally, in areas located even further laterally, meltwaters had almost no effect and the moraines were formed by plastering of till in the crevasses. The three faciès associations are part of a continuum beginning with the moraines composed of sorted sediments and grading laterally into the moraines formed of fissile and compact till. This continuum is described for the first time.